Analysis of the Effect of Leadership Style and Job Satisfaction on Organizational Commitment to Improve Employee Performance: Organizational Commitment as an Intervening Variable at PT. Niki Mapan Surabaya - Taqdirul Aziz; Sriyono Sriyono (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine the effect of leadership style and work leadership on organizational commitment to improve employee performance through both direct and indirect influence and to determine the effect of organizational commitment at PT Niki Mapan Surabaya. As many as 102 employees of PT Niki Mapan Surabaya as research samples. Analysis techniques used were path analysis, t-test statistics and F-test statistics. Data analysis was performed with the help of the SPSS program. The results showed that the leadership style and breadth of work affect the organizational commitment and employee performance, and organizational commitment affects the performance of employees of PT. Niki Mapam Surabaya.